PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS IX MTsN 1 PADANGSIDIMPUAN - Siregar, Hotnita Saputri (Departemen Matematika, 2024)
Good learning outcomes are the aim of mathematical education. Level IX MTsN 1 Padangsidimpuan TP. 2024/2025 students are only one example of how this goal is frequently discovered to be achieved in the other way. One possible approach is a cooperative learning strategy known as Two Stay Two Stray (TSTS). This study verifies that the model can outperform more traditional methods of instruction in terms of learning results. The Non-equivalent Posttest Only Control Group Design was the quasi-experimental method utilized. The study's sample population consists of students enrolled in TP 2024/2025's ninth grade at MTsN 1 Padangsidimpuan. Using Simple Random Sampling, the sample groups were chosen from classes IX-2 and IX-8. The rejection of the null hypothesis (H0) is indicated by a result of P-value = 0.001 below α, suggesting that the TSTS model outperforms conventional learning in terms of learning outcomes.Keywords- Two Stay Two Stray Type Cooperative Learning Model, Learning Outcomes.